Knowledge Assessment on Hazards of Plastic Use among Residents of Selected Urban Community of Pune City - Sheela Upendra1, Shital Waghmare2 , Mangesh Jabade3 , Diana Prasad3 , Jennifer W Anthony3, Stephina (Institute of Medico-legal Publications Pvt Ltd, 2020)
Introduction: Plastic products have become integral part of our daily lives. Due to which the production ofPlastic have gone up worldwide. Plastic consumption in India increased from 61 thousand tons in 1996 to1.78 million tons in 2017, which is a huge increase. Objective of the study is to assess the knowledge abouthazards of Plastic use among selected areas of Pune city. Methods: Non experimental descriptive surveyresearch design for the study. Sample comprised of 400 residents of selected urban community of Punecity. Non probability convenience sampling technique was used for the study. A self-administered structuredknowledge questionnaire on hazards of Plastic use was used. The tool is divided in two sections. Section Iis dealt with demographic proforma of the sample. Section II was self-administered structured knowledgequestionnaire comprised of thirty questions (Multiple choice questions) in four domains on knowledgeof hazards of plastic use, after permission from the concerned authority and informed consent from eachsample, the investigator has administered the tool. Result: Majority of respondents have average knowledge(46.75%) and 3.5% respondents had poor knowledge on hazards of Plastic use. Conclusion: The presentstudy revealed the residents had considerable average knowledge regarding hazards of plastic use. Theenhancement in knowledge is greatly required on all aspects of hazards of plastic use.